Processed line aerogravity data over the Institute and Moller region (2010/11 season) - Jordan, Tom; Ferraccioli, Fausto; Ross, Neil; Corr, Hugh; Leat, Philip; Bingham, Rob; Rippin, David; Le Brocq, Anne; Siegert, Martin (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
During the 2010/2011 Antarctic field season a collaborative NERC AFI (Antarctic Funding Initiative) project studying the basal boundary conditions of the Institute & Moller ice streams, West Antarctica, collected ~25,000 km of new high quality aerogravity data. Data were acquired using Lacoste and Romberg air-sea gravity meter S83, mounted in the BAS aerogeophysically equipped Twin Otter "Bravo Lima". Data are provided as XYZ ASCII line data. Data were collected as part of the UK Natural Environment Research Council AFI grant NE/G013071/1. : Airborne gravity are presented in Jordan et al., (2012) along with further details on data collection. The dataset available here includes all channels from raw through to filtered and upward continued free air anomalies. All data is provided in the "by flight" database. Data processing steps: 1/ Calculate observed gravity. True spring tension (ST_real) is calculated from the posted spring tension (ST) correcting for the fact that for this survey the true spring tension approaches the posted value at 38 mGal per second. Beam velocity (Beam_vel) is derived from raw beam position (RB) assuming a centred difference approximation. Relative gravity (rec_grav) = (Spr_tens_real+((beam_vel)*k_fac)+CC)*scale_value, k_fac=30, meter scale value =0.9966. Still readings (Still) are in mGal and were calculating assuming a 2nd order best fit to the approximately linear drift of the meter observed at the tie down points. Airborne absolute gravity values (Abs_grav) = Rec_grav- Still + Base 2/ Corrections to derive free air anomalies (disturbances). Vertical acceleration (VaccCor) is calculated as 2nd derivative of flight altitude (Height_WGS1984), with a 3 point mean filter applied after differencing to reduce short wavelength noise. Eotvos correction (EotvosCor) follows (Harlan, 1968). Latitude correction (LatCor) = 978.03185(1+0.005278895 sin2Lat- 0.000023462 sin4Lat) (IUGG 1967). Free air correction (FaCor) = 0.3086*Height_WGS1984. NOTE subsequent free air values are defined as gravity disturbances in geodesy, as they are referred to the ellipsoid (Hackney and Featherstone, 2003). Horizontal acceleration correction (HaccCor). For this survey the approximation of (Swain, 1996) was used, assuming a damping factor of 0.707, and a platform period of 4 minutes. 3/ Free air anomaly and filtering. Free air anomaly (Free_air) = Abs_grav-VaccCor+EotvosCor+FaCor-LatCor-(0.5*HaccCor) Filtered free air anomaly (FAA_filt) used 9 km 1/2 wavelength space domain kernel filter (Holt et al., 2006). Final free air data (FAA_clip) was produced by manually masking turns, start and end of lines, and other regions of noisy data. Levelling correction (level_cor) includes both statistical (line and tie) and microleveling (line only) of free air data. FAA_level includes data after levelling. Upward continued free air anomaly (FAA_2600) was produced by upward continuing free air data from the collected flight altitude to 2600 m. Channel description: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_no Line Number e.g. LW200.1:12 Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters * y y projected meters * Height_WGS1984 Aircraft altitude (meters) in WGS 1984 Raw gravity Channels ST Spring Tension (meter units) CC Cross Coupling (meter units) RB Raw beam position (Mv) XACC Cross axis accelerometer (Mv) LACC Long axis accelerometer (Mv) Still Airborne meter still reading value (mGal) Base Absolute gravity reference, from land gravity (mGal) Calculation Channels St_real True Spring tension value (meter units) Beam_vel Gravity meter beam velocity (Mv/sec) Rec_grav Recalculated relative gravity (mGal) Abs_grav Calculated absolute gravity (mGal) VaccCor Vertical acceleration correction (mGal) EotvosCor Eotvos correction (mGal) LatCor Latitude correction (mGal) FaCor Free air correction (mGal) HaccCor Horizontal acceleration correction (mGal) Free air Channels Free_air Un-filtered free air anomaly (mGal) FAA_filt Filtered free air anomaly (mGal) FAA_clip Filtered free air anomaly masked (mGal) FAA_level Filtered, masked and levelled free air anomaly (mGal) FA_2600m Upward continued free air anomaly (mGal) * Projected coordinates (x and y) are in Lambert conic conformal with two standard parallels defined as follows: Latitude of false origin: -82 Longitude of false origin: -14 Latitude of 1st standard parallel -84 Latitude of 2nd standard parallel -80 False easting 2000000 False northing 2000000 : 7.5 km line spacing survey.